Authors, peer reviewers, and readers: What is expected from each player in collaborative publishing? - Fernandez-Llimos, Fernando (2021)
Scholarly publishing is in a crisis, with the many stakeholders complaining about different aspects of the system. Authors want fast publication times, high visibility and publications in high-impact journals. Readers want freely accessible, high-quality articles. Peer reviewers want recognition for the work they perform to ensure the quality of the published articles. However, authors, peer reviewers, and readers are three different roles played by the same group of individuals, the users of the scholarly publishing system—and this system could work based on a collaborative publishing principle where “nobody pays, and nobody gets paid”.